HUBUNGAN POLA MAKAN DENGAN TEKANAN DARAH PADA ORANG HIPERTENSI DI PUSKESMAS BANJARDAWA KABUPATEB PEMALANG - Madjid, Sekar Zahra; Natalya, Wiwiek (Prosiding University Research Colloquium, 2024)
" Abstract Introduction The prevalence of hypertension in Central Java is the largest non- communicable disease, while according to the Pemalang District Health Office, the highest hypertension occurs in Taman District, especially the Banjardawa Health Center (93.05%). High blood pressure is closely related to people's diet. Uncontrolled eating patterns such as high sodium, high fat and lack of potassium trigger high blood pressure. The study aimed to determine the correlations between diet and high blood pressure at the Banjardawa Health Center. Method: The design of this study is correlation analytics, a cross-sectional approach, with accidental sampling techniques with a sample of 78 respondents, instruments using dietary questionnaires and sphygmomanometer tools to determine the correlation between diet and blood pressure using the Pearson product-moment test. Results: Respondents' diet mean (21.49). On systolic blood pressure, the respondents mean (159.40). At diastolic blood pressure, the respondents mean (92.83). The results of the hypothesis test using the Pearson product-moment test results of eating patterns with systolic blood pressure value 0.01 (<0.05) with a correlation value of r (0.290), the results of eating patterns with diastolic blood pressure value 0.01 (<0.05) with a correlation value of r ( 0.348). Accepted with a low correlation strength parameter, namely, there is a relationship between diet and blood pressure in hypertensive people at the Banjardawa Health Center, Pemalang Regency. Conclusion: A Correlation exists between diet and blood pressure in hypertensive people at the Banjardawa Health Center, Pemalang Regency. Suggestion: The Banjardawa Health Center health service is expected to further increase knowledge about a good diet for hypertension through health promotion. Keywords: Diet, Blood pressure, Hypertension Abstrak Latar Belakang: Prevelensi hipertensi di Jawa Tengah menepati penyakit tidak menular terbesar, sedangkan menurut Dinas Kesehatan Kabupaten Pemalang penyakit hipertensi tertinggi terjadi pada Kecamatan Taman khususnya Puskesmas Banjardawa sebanyak (93,05%). Tekanan darah tinggi erat kaitannya dengan pola makan masyarakat. Pola makan tidak terkontrol seperti mengkonsumsi natrium tinggi, lemak tinggi serta kurangnya kalium memicu terjadinya tekanan darah tinggi. Tujuan penelitian ini untuk mengetahui hubungan pola makan dengan penyakit tekanan darah tinggi di Puskesmas Banjardawa. Metode: Desaian penelitian ini adalah analitik korelasi, pendekatan cross sectional, dengan teknik accidental sampling dengan jumlah sampel 78 responden, instrumen menggunakan kuesioner pola makan dan alat sphygmanometer, untuk mengetahui hubungan pola makan dengan tekanan darah menggunakan uji pearson product moment . Hasil: Pola makan responden mean (21,49). Pada tekanan darah sistolik responden mean (159,40). Pada tekanan darah diastolik responden mean (92,83). Hasil uji hipotesis menggunakan uji pearson product moment hasil pola makan dengan tekanan darah sistolik pvalue 0,01 (<0,05) dengan nilai korelasi r (0,290), hasil pola makan dengan tekanan darah diastolik pvalue 0,01 (<0,05) dengan nilai korelasi r (0,348). Ha diterima dengan parameter kekuatan korelasi rendah yaitu terdapat hubungan pola makan dengan tekanan darah pada orang hipertensi di Puskesmas Banjardawa Kabupaten Pemalang. Simpulan: Terdapat hubungan pola makan dengan tekanan darah pada orang hipertensi di Puskesmas Banjardawa Kabupaten Pemalang. Saran : diharapkan kepada pelayanan kesehatan Puskesmas Banjardawa untuk lebih meningkatkan pengetahuan tentang pola makan yang baik untuk hipertensi melalui pemberian promosi kesehatan. "